Endocytosis restricts dendrite branching via removing ectopically localized branching ligands - Jie Fang; Wenli Jiang; Weixia Zhao; Jie Wang; Beibei Cao; Nan Wang; Baohui Chen; Chao Wang; Wei Zou (Nature Communications)
Abstract Neurons often grow highly branched and cell-type specific dendrite morphologies to receive and integrate information, which is the basis of precise neural circuit formation. Previous studies have identified numerous mechanisms that promote dendrite branching. In contrast, it is much less understood how this process is negatively regulated. Here we show that EAT-17/EVI5 acts together with the dynein adaptor protein BICD-1 and the motor protein dynein in C. elegans epidermal cells to restrict branching of PVD sensory dendrites. Loss-of-function mutants of these genes cause both ectopic branching and accumulation of the dendrite branching ligand SAX-7/L1CAM on epidermal plasma membranes. Mutants of genes regulating endo-lysosomal trafficking, including rab-5/RAB5 and dyn-1/DNM1, show similar defects. Biochemical characterization, genetic analysis, and imaging results support that EAT-17 and BICD-1 directly interact with each other and function in the endocytic degradation pathway to remove ectopically localized dendrite branching ligands to restrict abnormal branching.